Microbial and small zooplankton communities predict density of baleen whales in the southern California Current Ecosystem - Erin V. Satterthwaite; Trevor D. Ruiz; Nastassia V. Patin; Michaela N. Alksne; Len Thomas; Julie Dinasquet; Robert H. Lampe; Katherine G. Chan; Nicholas A. Patrick; Andrew E. Allen; Simone Baumann-Pickering; Brice X. Semmens (PLoS ONE, 2026)
Understanding the distribution and abundance of marine mammals is important for assessing population dynamics and evaluating the impacts of human activities on these species. Here, we assessed the capability of microbial and small plankton communities to predict the density of Balaenopteridae whales in the Southern California Current Ecosystem in each season from 2014 to 2020 using data from the California Cooperative Oceanic Fisheries Investigations (CalCOFI). Densities of Balaenopteridae whales were estimated from visual line transect surveys for three target species – blue ( Balaenoptera musculus ), fin ( Balaenoptera physalus ), and humpback ( Megaptera novaeangliae ) whales – and microbial and small plankton communities were examined in concurrent water samples via metabarcoding of the 16S and 18S rRNA genes. Planktonic communities specific to each target whale species appeared as strong statistical predictors of whale estimated density, explaining 81–99% of variability and predicting density estimates to within ~1 individual per 1000 km 2 . Our approach improved out-of-sample root mean square prediction error by up to 65% compared with simple alternative methods. Specific planktonic communities observed indicate that some predictor taxa may be ecologically associated with whales as parasites, as skin and respiratory microbiome species, or through the food chain of whale prey. However, further studies are needed to understand how these organisms function collectively as a community and interact with the “ecological habitat” that supports whales. Our results suggest that using planktonic communities to quantify the potential ecological habitat of larger organisms, like baleen whales, can enhance predictive models and may inform hypotheses about the ecological relationships between whales and the biological communities with which they co-occur.